Uso de plantas alimentícias e medicinais na Comunidade Indígena Nova Esperança, Terra Indígena São Marcos – Município de Pacaraima/Roraima - Mojica, Jennifer Barrera (2018)
Since the beginning of humankind, plants have been used as source of food and medicine. Traditional knowledge, as a way of knowing, it is based on na accumulation of observatios. Indigenous groups offer alternative knowledge and perspectives based on their own locally developed practices of resource use. The objective of this study was recording the use and management of food and medicinal plants used by the Nova Esperança indigenous community, localized at São Marcos indigenous land in Pacaraima- RR. Data about plant use were collected from 17 key informants (11 men and 6 woman) using semi-structured interviews and later, a sociocultural calendar was built using these data. In total, 80 plant species from 38 families were registered being the families Fabaceae, Arecaceae and Lamiaceae the most represented. From the registered families, 27 were cited as food and 27 as medicine. In regard with the plant origin, 46 species are native while 18 are exotic. Plant species were most commonly founded in ROÇA (28 species) following by backyard (23 species) and the most common plant habit were tree and herbaceous (33 species each one). These species are commonly collected from ROÇAS, backyards and natural environments (forest and savannah). Regarding the plants organs, leaves and bark are the most used to prepare medicines while the fruits are the most used as food. Medicinal plant species are used by informants for the treatment of 55 diseases, which were grouped into 12 categories of body parts proposed by ICD-10. Digestive system diseases (DSD) was the category with high species number being Gymnanthemum amygdalinum (“boldo”) the most cited species. Musculoskeletal and Conjunctive Diseases (MCD) were the diseases more treated using medicinal plants (ICF= 1). On the other hand, in relation with cultural importance, for the food category, banana (Musa spp.) and cassava (Manihot esculenta) were the most important (CI= 0.76 and CI= 0. 71, respectively) while “salva do campo” (Lippia microphylla) was the most important for medicinal category (CI= 1.59). Additionally, several ethnovarieties of banana and cassava were found. The results from this work evidence that Nova Esperança indigenous community still use their ancestral practices and knowledge since, besides to use local plant species, also, they cultivate plant species from their homeland.